Methods for county spatial planning in pastoral rangelands in Kenya for strengthened land rights and improved management of natural resources - CGIAR Research Program on Livestock (2019)
Research carried out under the Livestock CRP and other ILRI projects informed the development of the methodology, which has been documented and the guidelines disseminated. There are plans to carry out, in 2020, training workshops based on materials.